82 Out of sight but not out of mind. A district hospital cardiology teleclinic setup… patients', sustainability and environmental benefits. (4th June 2021) - yao, zhihong; Farag, Ahmed; Mullineux, Pauline; Matthews, Wendy; Carimichael, Mark; Barlow, Chris
Abstract : Introduction: The ever-greater prevalence of cardiovascular disease has placed increasing pressure on cardiology services in the UK to achieve higher efficacy and improved quality of care. Telemedicine is emerging as a cost effective way to enhance patient's care. With the COVID19 pandemic, vitual-consultation had been became more widely used. The effectiveness and safety of tele-health intervention in cardiovascular condition in the UK remains unclear. Aim: To describe our early experience and outcomes setting up virtual teleconsultation for stable follow up cardiology patients in a district general hospital. Method: Since April 2019, a single cardiologist (AF) started enrolling selected stable cardiology follow up patients onto the virtual follow-up. Following the initial standard consultation, the results of the investigations would be reviewed by the attending cardiologist and subsequent consultation would be carried out via pre-arranged telephone appointment if patients are agreeable. Patient's outcomes and satisfaction survey were collated, sustainability and social benefits and environmental impact of the pilot were analysed. Result: A total of 116 patients were enrolled into the pilot. Fifty eight percent were males with an average age of 67 years (range 26-93). Conditions enrolled were: stable ischaemic heart disease (put numbers and percentage 42%), Stable valvular heart disease (26%), arrhythmias (13%), heart failure (9%) and others (9%). Sixty patients (52%) were discharged and 42% (49) patients had further routine tele-clinic follow-up. There were 6% (7) patients failed to attend the telephone consultation. Patients feedback was overwhelmingly positive with the main themes being: Convenience, avoiding car parking congestion, avoiding traffic / transportation issues as well as avoiding overall visit costs. The main concerns raised in patients using tele-consultation were related: 1) Mobile phone connectivity 2) Privacy issues and 3) Logistic of completing pre-requisite investigation prior appointment. Figure 1 demonstrates the clinic's sustainability benefits. The did not attend (DNA) rates were significantly less compared to standard clinic (5.8% vs 8.2%). This pilot saved the trust c.a £3000 on consumables and logistics support and maximised outpatient clinic capacity utilisation. Conclusion: Telemedicine had been shown to be a safe and effective method in the care of stable cardiology patients. The social, economic and environmental benefit of tele-consultation raised exciting opportunity for future service designs. Collaboration between hospital specialist, management team, community health providers and communication service suppliers are vital to ensure the sustainable implementation of telemedicine in cardiology. Conflict of Interest: none